Power Asymmetry in Credit Dispute Resolution and the Role of Notaries in Mediating Bank–Debtor Relations - Muhammad Hafid Arisanto (Universitas Darul Ulum, 2026)
This study employs a qualitative socio-legal approach using a narrative literature review to examine power asymmetry in credit dispute resolution, focusing on the role of notaries in mediating bank–debtor relations. Existing studies have emphasized legal certainty and contractual arrangements, while limited attention has been given to power dynamics in negotiation and dispute resolution processes. Data were drawn from legal, economic, and institutional literature and analyzed thematically to identify patterns of power relations, intermediary roles, and dispute resolution mechanisms. The findings show that power asymmetry is structurally embedded through contractual dominance, information asymmetry, institutional legitimacy, and relational networks favoring banks. Within this structure, notaries occupy an ambivalent position as intermediaries, acting as mediators, facilitators, and, in some contexts, reproducers of power imbalance. Credit dispute resolution is therefore not a neutral legal process but a negotiation arena shaped by unequal access to resources, information, and authority. This study argues for a shift from a legal-formal perspective toward a power-centered analytical framework. By conceptualizing notaries as multifunctional intermediaries, the study contributes to socio-legal scholarship and offers practical insights for promoting fairness in credit systems and dispute resolution.